2021
DOI: 10.1177/11297298211033508
|View full text |Cite
|
Sign up to set email alerts
|

Study on prediction of arterio-venous fistula maturation by flow mediated dilatation and AVF blood flow

Abstract: Background: The physiology and pathology of AVF maturation depends on the vessels characteristics and its ability to remodel. Outcome of AVF using flow mediated dilatation (FMD), AVF blood flow and diameter has been studied. Methodology: Present observational study included single stage AVF (both Radiocephalic and Brachiocephalic) in consecutive CKD five patients ( n = 158) prospectively over 1 year. Demographic and Doppler ultrasound parameters of upper limb (for vessel diameter and FMD) at baseline were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Intimal hyperplasia is the main stenosis lesion and the leading cause of AVF non maturation [ 54 ]. It has been associated with endothelial dysfunction both in vivo and in vitro [ 55 , 56 , 57 ]. In the multicenter prospective Hemodialysis Maturation Fistula Study, interventions performed for AVF stenosis were the most frequent interventions aiming to facilitate AVF maturation [ 53 ].…”
Section: Antiphospholipid Mediated Avf Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intimal hyperplasia is the main stenosis lesion and the leading cause of AVF non maturation [ 54 ]. It has been associated with endothelial dysfunction both in vivo and in vitro [ 55 , 56 , 57 ]. In the multicenter prospective Hemodialysis Maturation Fistula Study, interventions performed for AVF stenosis were the most frequent interventions aiming to facilitate AVF maturation [ 53 ].…”
Section: Antiphospholipid Mediated Avf Complicationsmentioning
confidence: 99%
“…vitro [55][56][57]. In the multicenter prospective Hemodialysis Maturation Fistula Study, interventions performed for AVF stenosis were the most frequent interventions aiming to facilitate AVF maturation [53].…”
Section: Avf Maturationmentioning
confidence: 99%
“…However, one potential limitation of US maturation assessment is the lack of a clearly defined optimal location for blood flow measurements [16]. Clinical maturation refers to the capacity of a fistula to be used for hemodialysis with two large-gauge needles for at least 75% of a patient's dialysis sessions over a 2-week period [17]. Previous studies have demonstrated that clinical maturation can be accurately predicted by palpation of a thrill in the cannulation zone during physical examination in 72% to 80% of patients [18].…”
Section: Us Assessment Of Fistula Maturationmentioning
confidence: 99%